Coffee Sustainability in Kenya: Role Played by Improved Varieties - Gichimu, Bernard M. (My University, 2015)
Coffee production in Kenya has been sinking since 1980s. The condition has been worsened by climate change phenomenon which has brought new production challenges in recent years. The biggest challenge is the changing dynamics of coffee pests and diseases, for example, Coffee Leaf Rust, which has become of a major concern globally. Variety improvement through breeding is believed to be one of the most sustainable ways of reducing production costs and mitigating climate change. Over the years, considerable success has been made in Arabica coffee breeding to improve yields, quality and to manage some biotic and abiotic stresses. Kenya produces mainly Arabica coffee from five commercial cultivars. These include three traditional varieties namely SL28, SL34 and K7, all of which are also susceptible to major coffee diseases, and two improved varieties namely Ruiru 11 and Batian. Owing to the current production challenges and the rising demand of Kenyan coffee in the world market, improved Arabica coffee cultivars with better quality, higher yield potential, resistance to diseases and tolerant to drought are largely replacing traditional varieties on a large scale in Kenya. This paper highlights the foreseeable role of these improved varieties in reversing the tumbling production trend and ensuring coffee sustainability in Kenya.
Keywords: Arabica Coffee, Improved Varieties, Climate Change, Kenya